Reconfigurable Multi-Legs Robot For Pipe Inspection: Design And Gait Movement - Ab Rashid, Mohd Zamzuri; Mohd Yakub, Mohd Fitri; Shaikh Salim, Sheikh Ahmad Zaki; Ali Mat, Mohamed Sukri; Mamat, Normaisharah M.; Mohd Putra, S. M. S.; Roslan, Shairatul Amni Husna; Mohd Shah, Hairol Nizam; Mohd Aras, Mohd Shahrieel; Arshad, Mohd Rizal (National Institute Of Science Communication And Information Resources (NISCAIR), 2019)
This paper focuses on studies on reconfigurable multi-legs robotic system. The aim of this paper is to identify and acquire findings on how multi-legs robot can walk, climb vertical pipe and walk along the horizontal pipe after climbing. Three degrees of freedom (3DOF) multi-legs robot is designed and built to replace human involvement either at hazardous pipeline or to check on vertical and horizontal pipes. The robot system is tested to climb the vertical pipe and then move along horizontal pipe for inspection or other purposes. This can reduce the cost and percentage of human risk exposure during inspection on outer pipe. This multi-legs robot has more movement gaits compared to wheeled robot, but in terms of speed, wheeled robot possesses greater advantages. Therefore, this system design has combination of both wheel and multiple legs ensure that the to system has higher stability, more gait movement, and higher speed manoeuvrability. The gaits analysis for the system movement includes angle of the legs to move and selection of certain legs to perform a given operation, either walking, climbing or hanging. The target result is the system able to climb 500 mm height with 85 mm radius pipe. The potential applications for the system are: (i) to move along either on surface or underwater pipe and (ii) to be equipped with ultrasonic sensor to inspect the pipe.